Highly Innovative Mental Health Digital Business Flashbox - Handoko, Mahardika Maulana Al Mahdi; Rabbani, Muhammad Fathi (East Asian Journal of Multidisciplinary Research, 2024)
In the realm of digital mental health, Flashbox has emerged as an innovative startup, revolutionizing the way mental health services are accessed and delivered. This abstract delves into the novel business strategies and technological advancements that Flashbox has implemented to address the growing demand for mental health services in the digital age. Emphasizing user-centric approaches, Flashbox integrates cutting-edge technology such as AI, machine learning, and user-friendly digital platforms to enhance the accessibility and effectiveness of mental health care. The startup uniquely navigates the challenges of stigma, accessibility, and affordability in mental health, offering a range of services from online counseling to mental health self-assessment tools. Flashbox's contribution to digital mental health underscores the importance of technology-driven solutions in improving mental health outcomes and offers a model for other startups in this sector. This study highlights Flashbox's role in transforming the landscape of mental health services, marking a significant step towards more inclusive, efficient, and accessible mental health care solutions.